Issues of regulations of ethnic minorities in contemporary political processes: Western Experience and current Georgia - Abashidze, Zviad (Politics / პოლიტიკა; 2021: მეექვსე ნომერი, 2021)
The given article discusses the issues of regulations and basic models of accommodation of ethnic minorities in contemporary Western liberal democracies and its correlation to current Georgia. Current increasing emigration processes vis a vis origination of far rights movements in western democracies have been somehow shifted conventional ways of understanding of nation-state and ethnic coexistence, especially in East-Central Europe and even in old democracies, but from our point of view, the radical shift of traditional cores of traditional political stability requires long time and is not pretty real in short term perspectives. Therefore, for Georgia, whos’ crucial challenge for successful democratic state-building remains it’s ethnic diversity, the consideration of western conventional experience of civic integration and coexistence has been still actual.
Keywords: minorities/ethnic minorities; civic integration; nation-state; multiculturalism.